ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI BANGUN RUANG SISI DATAR MENURUT PROSEDUR NEWMAN DI KELAS VIII SMP NEGERI 2 LANGOWAN - Makalunsenge, Khofifah Indar Parawansa; Tumalun, Nicky Kurnia; Wenas, Jhon Robby (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The purpose of this study is to describe the errors experienced students in solving word problems on the material on the flat side of the classroom VIII SMP Negeri 2 Langowan based on the Newman procedure. This research using this type of qualitative research, with the methods used in data collection, namely written tests in the form of essay, interviews, and documentation. The subjects in this study were class VIII C students 26 students. Based on the results of the data obtained, it shows that in solving word problems on flat sided space material, students make mistakes at the stage of understanding the problem (comprehension) with a percentage og 18,4, this stages of process transformation (transformation) with a percentage of 28,4%, the stages of process skills (process skills) with a percentage of 44,6%, and the stages of writing the final answer (endcoding) with a percentage of 51,5%.